2015
DOI: 10.1103/physrevb.92.045211
|View full text |Cite
|
Sign up to set email alerts
|

Systematic approach for simultaneously correcting the band-gap andpdseparation errors of common cation III-V or II-VI binaries in density functional theory calculations within a local density approximation

Abstract: We propose a systematic approach that can empirically correct three major errors typically found in the density functional theory (DFT) calculation within a local density approximation (LDA) simultaneously for a set of common cation binary semiconductors, such as III-V compounds -(Ga or In)X with X=N, P, As, Sb, and II-VI compounds (Zn or Cd)X, with X= O, S, Se, Te. By correcting (1) the binary bandgaps at high symmetry points Γ, L, X, (2) the separation of p and d orbital derived valence bands, and (3) conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…This is because DFT-1/2 lowers the O 2p orbital with respect to Zn 3d. Hence, they proposed that the self-energy potential for Zn 3d should be enhanced to first obtain a correct location for Zn 3d states, as proper p-d separation is the prerequisite of treating similar II-VI semiconductors [146]. It was found that the location of 3d states is linear with the amplitude A, as illustrated in figure 11.…”
Section: Dft+a-1/2mentioning
confidence: 99%
“…This is because DFT-1/2 lowers the O 2p orbital with respect to Zn 3d. Hence, they proposed that the self-energy potential for Zn 3d should be enhanced to first obtain a correct location for Zn 3d states, as proper p-d separation is the prerequisite of treating similar II-VI semiconductors [146]. It was found that the location of 3d states is linear with the amplitude A, as illustrated in figure 11.…”
Section: Dft+a-1/2mentioning
confidence: 99%
“…On the basis of the above analysis, it is inappropriate to introduce the elements aluminum, phosphorus, and arsenic. The reason is that the bandgap energy of the alloy should be enlarged and its SOP energy will be lowered after introducing these elements as the bandgap energies of GaP, GaAs, and AlSb are larger while the SOP energies of GaP, GaAs, and AlSb are smaller than those of GaSb [24]. We notice that the bandgap energy of InSb is much smaller than that of GaSb.…”
Section: Physical Model and Discussionmentioning
confidence: 91%
“…Pronounced hydrogenic1s, 2s lines were observable even at room temperature, the (so)-e transition smeared out after heating over 200 K. However, the spectral separation of these bands was in the range of 70 meV. To undoubtedly resolve the question of the origin of the absorption features in our spectra, we performed ab initio calculations (see Methods section) [41][42][43][44][45] of the WZ ZnS slab with [11][12][13][14][15][16][17][18][19][20] growth direction and 1.91 nm width (5 MLs), which corresponds to the average width of the NPLs measured with TEM. From the theoretical simulation of the dipole transitions using Γ-point wave functions, we can conclude that the first absorption peak corresponds to a sum of three transitions, namely from the nodeless states derived from the A-, B-and C-bulk valence (WZ) bands to the nodeless conduction band minimum state (CBM).…”
Section: Resultsmentioning
confidence: 99%